Class act [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel (Sound recording), 2021)
After a rocky jaunt in Maine, Stone Barrington is settling back in New York City when an old client reaches out for help with a delicate matter. A feud they thought was put to rest long ago has reemerged with a vengeance, and reputations--and money--are now on the line.